2017
DOI: 10.1007/s10508-017-1055-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of HIV Disclosure Behavior Following a Randomized Controlled Disclosure Intervention for Men Who Have Sex with Men Living with HIV

Abstract: Preventing the transmission of HIV, especially among high-risk populations, is a U.S. public health priority. Interventions aimed at easing the burden of HIV disclosure to casual sexual partners among men who have sex with men (MSM) living with HIV are essential in this endeavor. This randomized controlled study evaluated differences in disclosure behavior between a disclosure intervention (DI) and attention control case management (ACCM) group for MSM living with HIV (N = 315) and determinants (self-efficacy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Among participants living with HIV infection, we found that confidants' awareness of participants' HIV status was positively associated with being virally suppressed. To date, most studies that examine HIV serostatus disclosure among MSM only focus on disclosure within sexual partnerships [48][49][50]. Our finding further extends the understanding of HIV status disclosure within close personal networks.…”
Section: Discussionsupporting
confidence: 66%
“…Among participants living with HIV infection, we found that confidants' awareness of participants' HIV status was positively associated with being virally suppressed. To date, most studies that examine HIV serostatus disclosure among MSM only focus on disclosure within sexual partnerships [48][49][50]. Our finding further extends the understanding of HIV status disclosure within close personal networks.…”
Section: Discussionsupporting
confidence: 66%
“…Other considerations may include collaboration with victim services, social work and housing—especially for those persons living with HIV, and other intersecting sociostructural challenges (e.g., Katz et al, 2013). Unfortunately, efforts to develop safe disclosure practices have not successfully lead to increased disclosure (Kennedy, Haberlen, Amin, Baggaley, & Narasimhan, 2015; Serovich, Laschober, Brown, & Kimberly, 2018). In their systematic review, Kennedy and colleagues (2015) identified only two empirically sound intervention studies on safe disclosure for persons living with HIV.…”
Section: Principle II Responsible Caringmentioning
confidence: 99%
“…Disclosure of positive HIV serostatus enables sexual partners of PLWH to make informed choices regarding acceptable levels of HIV transmission risk. As such, sexual partner disclosure has been targeted as an important component of prevention interventions in PLWH (Chiasson, Shaw, Humberstone, Hirshfield, & Hartel, 2009;Conserve, Groves, & Maman, 2015;Kalichman et al, 2001;Serovich, Laschober, Brown, & Kimberly, 2017) . Such interventions propose that if non-HIV-positive sex partners are informed of their acute risk of HIV transmission, they will be more motivated to implement HIV prevention strategies such as condom use.…”
Section: Hiv Partner Disclosurementioning
confidence: 99%